2012
DOI: 10.5204/jld.v6i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural affordances of online peer engagement

Abstract: University learning increasingly includes online learning experiences embedded within teaching with the dual policy intentions of increasing flexibility and learner engagement. In this research project, three university lecturers from different teaching contexts selected technologies for online learning to enhance learner engagement by encouraging peer learning. A sociocultural view of learning was used to conceptualise the technological and social affordances that might enable student peer participation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Parker et al (2006) assume social interaction with peers as a major component for developing children's social competence, and research studies also show that children who have poor social interaction with peers lead to a greater risk of experiencing loneliness in later life (Neighbourhood et al, 2010). Peers can create a sense of security, support, belongingness, a sense of learning or can create opportunities for learning for an individual (Willis et al, 2013).…”
Section: Peer Engagementmentioning
confidence: 99%
“…Parker et al (2006) assume social interaction with peers as a major component for developing children's social competence, and research studies also show that children who have poor social interaction with peers lead to a greater risk of experiencing loneliness in later life (Neighbourhood et al, 2010). Peers can create a sense of security, support, belongingness, a sense of learning or can create opportunities for learning for an individual (Willis et al, 2013).…”
Section: Peer Engagementmentioning
confidence: 99%
“…However, despite these features, there are still some constrains that limit students from using the online learning. Willis, Davis, and Chaplin (2013) have pointed common barriers prevent students from participating in online learning and make them prefer traditional courses. On the other hand, these barriers are considered as huge lack of familiarity with a new environment, structure, material and strategy, as well as a lack of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Affordance theory has been widely applied in the design of educational artifacts and digital learning tools (Dalgarno & Lee, 2010;Mavrikis, Noss, Hoyles, & Geraniou, 2012). An increasing number of educational technology researchers have explored various information and communication technologies (ICTs) related interventions to uncover the mechanisms of how the affordances of educational technologies could be used to facilitate learning engagement (Willis, Davis, & Chaplin, 2013) and performances improvement (Limperos, Buckner, Kaufmann, & Frisby, 2015). For example, based on affordance enrichment perspective, Weidlich and Bastiaens (2019) designed an online learning environment that affords social presence to improve learning performance, which significantly improved learners' satisfaction and learning achievement.…”
Section: British Journal Of Educational Technology Vol 51 No 5 2020mentioning
confidence: 99%
“…Existing studies have investigated the antecedents of engagement in various online communities (Brodie, Ilic, Juric, & Hollebeek, 2013;Gavilanes et al, 2018), research found that engagement is associated with internal feelings of and cognitive perceptions on the learning processes/environment (Li & Song, 2018;Xie et al, 2019). In a traditional online learning environment, affordances were found to be related to learning engagement (Willis et al, 2013). In the study of Willis et al (2013), the social structures and technological affordances of online learning environment provide reflective discussion opportunities to learn, which lead to high levels of engagement reported by learners' active participation and sense of belongings on the digital learning tool.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation